HISTORICAL AND FUNCTIONAL ANALYSIS IN ARCHITECTURE: CASE STUDY OF VREDEBURG FORT YOGYAKARTA - Romadhonita, Novia; Rachmalia, Indah (ADBE, 2025)
Yogyakarta has grown in line with the progress of time and technology. Vredeburg Fort, located in the center of Yogyakarta City, was originally built as a defense fort and served as a surveillance fortress constructed by the Vereenigde Oostindische Compagnie. In order to examine its history and functionality, this research was conducted using a comprehensive analysis method, including a case study of the building through historical literature studies, field observations, and architectural analysis of Vredeburg Fortress. The analysis results indicate that functionally, Vredeburg Fort has shifted from a defense fortress and observation tower to a museum storing historical items, particularly those related to Yogyakarta City. However, historically, Vredeburg Fortress still retains its history both in terms of visible architectural features and written records. This research contributes to the examination of the shift in function of the fortress from its original military stronghold to a cultural center and museum.